2021
DOI: 10.3390/vision5040057
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Network of the Visual Cortex Is Altered in Migraine

Abstract: Migraine is a common neurological disorder characterized by recurrent episodes of headache, frequently accompanied by various reversible neurological disturbances. Some migraine patients experience visually triggered migraine headache, and most attacks of migraine with aura are associated with the disturbance of vision and photophobia, suggesting an abnormal neural activity in the visual cortex. Numerous studies have shown a large cortical hemodynamic response to visual stimulation and an altered intrinsic vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It is also important to consider whether the goal of potential collaborators in using fMRI to study headache is the development of new experimental methods or whether it is disease characterization. An example of new methods development is a recent paper demonstrating a novel method of identifying functional networks, dubbed functional areas of unitary pooled activity by the authors, in the visual cortex in patients with migraine versus healthy controls 163 . It is often desirable to demonstrate a new imaging method on a well‐characterized disease state such as migraine.…”
Section: Methods Of Fmri Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to consider whether the goal of potential collaborators in using fMRI to study headache is the development of new experimental methods or whether it is disease characterization. An example of new methods development is a recent paper demonstrating a novel method of identifying functional networks, dubbed functional areas of unitary pooled activity by the authors, in the visual cortex in patients with migraine versus healthy controls 163 . It is often desirable to demonstrate a new imaging method on a well‐characterized disease state such as migraine.…”
Section: Methods Of Fmri Researchmentioning
confidence: 99%
“…An example of new methods development is a recent paper demonstrating a novel method of identifying functional networks, dubbed functional areas of unitary pooled activity by the authors, in the visual cortex in patients with migraine versus healthy controls. 163 It is often desirable to demonstrate a new imaging method on a well-characterized disease state such as migraine. In contrast, an example of disease characterization is a recent task-based fMRI study of trigeminonociceptive stimulation with ammonia in patients with cluster headache, using established methods for brainstem imaging and an established ammonia stimulation protocol.…”
Section: Considerations If Asked To Collaborate On Fmri Researchmentioning
confidence: 99%
“…The visual network has been strongly linked to migraine. Recently, Huang and Wilkins demonstrated that the distribution of the visual network was altered in migraine patients and demonstrated lateralization [61]. In another study, there was enhanced FC between the thalamus and several parts of the visual cortex, suggesting aberrant projections from the thalamus to the visual network [62].…”
Section: Alterations In Multiple Network Underlie Migrainementioning
confidence: 98%